The relationship between Gratitude and Life satisfaction in a sample of Spanish university students - Salvador-Ferrer, Carmen (Anales de Psicología / Annals of Psychology, 2016)
The aim of this study is to examine the relationship between gratitude and life satisfaction among university students in Spain. The present study seeks to assess gratitude by means of a self-report Gratitude Questionnaire (GQ-6; McCullough et al., 2002) and Life satisfaction scale (SWLS; Diener et al., 1985). Using a multiple linear regression analysis, the relationship between life satisfaction and gratitude is analyzed. The results suggest that gratitude significantly predicts life satisfaction, while on the other hand, differences exist with regard to gender in the relationship between gratitude and life satisfaction. The significance and limitations of the present findings are discussed.